Analysis of PTEN expression in large intestine polyps and its relation to the recognized histopathological and clinical risk factors for cancer development in this location - Waniczek, Dariusz; Śnietura, Mirosław; Pigłowski, Wojciech; Rdes, Jerzy; Kopeć, Agnieszka; Młynarczyk-Liszka, Joanna; Rudzki, Marek; Hudyka, Krystyna; Arendt, Jerzy; Lange, Dariusz (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : PTEN is an important gene whose protein product is double specific phosphatase holding key regulatory functions in sending signals from membrane receptors for growth factors into the cell downstreams. Its participation, mainly by PI3K/AKT signaling pathway in the pathomechanism of many malignant cancers was unambiguously confirmed. The PTEN function gets disturbed on many levels and for various reasons. Disorders of PTEN protein expression seem to be even more common in many carcinomas. The aim of the study is to enquire the meaning of PTEN expression in the cancer transformation process in large intestine glandular polyps. Material and methods : The group includes 40 patients, 21 men and 19 women, age median 64 years (51–83) qualified to endoscopic removal of large intestine polyp. Tissue material obtained during polyp removal endoscopy was immediately fixed in 4% buffered formalin solution with the mixture of phosphatase activity inhibitors (PhosStop Roche). Time of fixation 24–48 h. After fixation, the material was embedded in paraffin. PTEN visualization was based on specific rabbit monoclonal antibodies (Cell Signaling). The expression of PTEN protein in large intestine and rectum polyps was marked by a semi-quantitative method and an attempt to correlate the results with the acknowledged clinical and histopathological malignancy risk factors was undertaken. Results : Loss or weakening of protein expression was found in 45% cases. Moreover, the relationship between polyp diameter and a loss of PTEN expression was proved. The received results can indicate a significant participation of PTEN gene in early oncogenesis stages of large intestine cancer.